Effects of combined soil amendments on the availability and migration of Cd in soil and rice - Jie Yang; Zhu Zou; Hongquan Yang; Junyi Wu; Zile Yang; Chaoxu Fang; Xiangdong Wei (Frontiers in Environmental Science)
To achieve safe production of severe cadmium (Cd)-contaminated paddy fields, the effects of a combination of red mud, silicon fertilizer, and phosphorus fertilizer on the absorption, transportation, and accumulation of Cd in rice were studied by a field plot orthogonal experiment. The results showed that soil pH, biomass of straw, and grain increased after applying the combined soil amendments. Compared with the control (CK), soil-available Cd decreased by 16.90%–47.09%. Cd content decreased by 42.30%–65.62% in roots, 16.05%–67.98% in stems, 26.09%–66.30% in leaves, and 48.39%–74.19% in grain. Variance and range analysis showed the effect of the three amendments on Cd reduction in grain was in descending order: red mud > silicon fertilizer > phosphate fertilizer. The optimal combination of soil amendments to control Cd pollution was 1,800 kg/ha red mud, 600 kg/ha silicon fertilizer, and 675 kg/ha phosphorus fertilizer. Results showed that safe production from severely Cd-contaminated paddy fields could be achieved by applying a combination of soil amendments and provided a method for remediating a severely Cd-contaminated paddy field.